Variability in the Essential Oil Composition of Achillea erba‐rotta subsp. moschata (Wulfen) I. Richardson Growing in the Eastern Italian Alps. Issue 11 (3rd November 2022) - Fusani, Pietro; Aiello, Nicola; Biazzi, Elisa; Tava, Aldo
Abstract: Achillea erba‐rotta subsp. moschata (Wulfen) I. Richardson is endemic of the Central Alps and distributed in several Italian Regions, where is used for its medicinal and aromatic properties. Nine wild populations of the species were characterized for their essential oil content and composition. In total 45 components were detected of which 40 were identified, accounting from 96.3 % to 98.8 % of the total oil. Monoterpenes represented the main class of compounds (from 84 % to 90.9 %), being cis‐ thujone (from 1.1 % to 48.4 %), camphor (from 1.8 % to 36.9 %), 1, 8‐cineole (from 4.9 % to 23.4 %), trans‐ thujone (from 2.2 % to 33.9 %) and p‐ cymene (from 1.8 % to 4.8 %) the most abundant ones. The relative amount of chamazulene, detected in some accessions, was here reported for the first time in this species. High variability in the essential oil composition resulted among the investigated accessions, which were grouped by multivariate analysis into four main clusters, in some cases according to their site of origin. Beyond their possible chemo‐systematic significance, the obtained results represent useful indications for the selection of interesting chemotypes within the species, especially in the perspective of its future cultivation. Abstract :